Corporate social responsibility reporting of two note-issuing banks in Hong Kong - Freda Hui; Graham Bowrey (Australasian Accounting, Business and Finance Journal, 2008)
The environmental performance and management disclosure of organisations came under increased scrutiny over the past decade due to several factors, particularly the impact organisations have on the world’s environment and the rapid change in the world’s climate. These concerns prompted organisations, including financial institutions, to review the level of their environmental performance and management disclosures to demonstrate, amongst other objectives, their level of social responsibility. Due to the nature of their business, financial institutions are not generally seen to contribute directly to the degradation of the environment; however, they do provide the funds for many organisations’ projects which directly affect the environment. This paper reviews the environmental performance and management disclosure developments in China specifically by two note-issuing banks in Hong Kong: the Hongkong and Shanghai Banking Corporation (HSBC) and the Bank of China (Hong Kong) Limited (BOCHK) from 2003 to 2006. The review is conducted with reference to the Equator Principles, a voluntary environmental performance framework developed specifically for financial institutions. The paper also contributes to the literature on legitimation theory, using a social constructionalist perspective of legitimation.
Keywords: Environmental reporting; equator principles; legitimation; Hongkong and Shanghai Banking Corporation (HSBC); Bank of China